THE EFFECT OF PRODUCT PACKAGING AND PRICE ON ONLINE PURCHASE DECISIONS OF SME PRODUCTS WITH PURCHASE INTEREST AS INTERVENING VARIABLES (CASE STUDY ON ONLINE BUYERS OF FOOD AND BEVERAGE SME PRODUCTS IN MAKASSAR CITY) - atirah ridwan (Scientia Integritas Utama, 2022)
This study aims to determine the effect of product packaging and price on online purchasing decisions for SME products through purchase intention as an intervening variable. This research is quantitative, and the data used is primary data, namely, data obtained from distributing questionnaires to research subjects. The population in this study are consumers who have purchased SME products online in Makassar. The sampling technique used was purposive sampling with a total sample of 100 respondents. The analytical method used in this study is the partial least squares PLS method with the help of the SmartPLS 3.0 program. The study's findings indicate that (1) packaging has a positive and significant effect on interest in purchasing SME Makassar products; (2) prices have a positive and significant effect on interest in purchasing Makassar City SME products; (3) packaging has a positive and significant effect on online purchasing decisions for Makassar City SME products; and (4) price does not have a positive and significant effect on online purchasing decisions for Makassar City SME products. (5) Interest in buying has a positive and significant effect on online purchasing decisions for Makassar City SME products; (6) packaging has a positive and significant effect on online purchasing decisions through interest in buying Makassar City SME products; and (7) price has a positive and significant effect on online purchasing decisions through interest in buying Makassar City SME products.